Structural and mechanistic insights into bisphenols action provide guidelines for risk assessment and discovery of bisphenol A substitutes - Delfosse, Vanessa (National Academy of Sciences, 2012)
Bisphenol A (BPA) is an industrial compound and a well known endocrine-disrupting chemical with estrogenic activity. The widespread exposure of individuals to BPA is suspected to affect a variety of physiological functions, including reproduction, development, and metabolism. Here we report that the mechanisms by which BPA and two congeners, bisphenol AF and bisphenol C (BPC), bind to and activate estrogen receptors (ER) α and β differ from that used by 17β-estradiol. We show that bisphenols act as partial agonists of ERs by activating the N-terminal activation function 1 regardless of their effect on the C-terminal activation function 2, which ranges from weak agonism (with BPA) to antagonism (with BPC). Crystallographic analysis of the interaction between bisphenols and ERs reveals two discrete binding modes, reflecting the different activities of compounds on ERs. BPA and 17β-estradiol bind to ERs in a similar fashion, whereas, with a phenol ring pointing toward the activation helix H12, the orientation of BPC accounts for the marked antagonist character of this compound. Based on structural data, we developed a protocol for in silico evaluation of the interaction between bisphenols and ERs or other members of the nuclear hormone receptor family, such as estrogen-related receptor γ and androgen receptor, which are two known main targets of bisphenols. Overall, this study provides a wealth of tools and information that could be used for the development of BPA substitutes devoid of nuclear hormone receptor-mediated activity and more generally for environmental risk assessment.